Plasma procalcitonin in rheumatic diseases - C.A. Scirè; R. Caporali; C. Perotti; C. Montecucco (PAGEPress Publications, 2003)
Data on the origin and biological function of procalcitonin, the pro-hormone of calcitonin, are scarce. Since this peptide can be induced in bacterial invasive infections, serum procalcitonin levels may be useful in differential diagnosis of systemic inflammatory response syndrome. This review will focus on the clinical significance of changes in serum procalcitonin levels in patients with connective tissue diseases and other rheumatic disorders.